Migration-associated malaria from Africa in southern Spain - Pousibet-Puerto, Joaquín (Parasit Vectors, 2021)
BACKGROUND: The western area of the province of Almeria, sited in southern Spain, has one of the highest immigrant population rates in Spain, mainly dedicated to agricultural work. In recent years, there has been a significant increase in the number of cases of imported malaria associated with migrants from countries belonging to sub-Saharan Africa. The objective of our study is to describe the epidemiological, clinical and analytical characteristics of malaria patients treated in a specialized tropical unit, paying special attention to the differences between VFR and non-VFR migrants and also to the peculiarities of microscopic malaria cases compared to submicroscopic ones. METHODS: Retrospective observational study of migrants over 14 years of age with imported malaria treated from October 2004 to May 2019. Characteristics of VFR and non-VFR migrants were compared. Malaria cases were divided into microscopic malaria (MM) and submicroscopic malaria (SMM). SMM was defined as the presence of a positive malaria PCR test together with a negative direct microscopic examination and a negative rapid diagnostic test (RDT). Microscopic malaria was defined as the presence of a positive RDT and/or a positive smear examination. RESULTS: Three hundred thirty-six cases of malaria were diagnosed, 329 in sub-Saharan immigrants. Of these, 78.1% were VFR migrants, in whom MM predominated (85.2% of cases). In non-VFR migrants, SMM represented 72.2% of the cases. Overall, 239 (72.6%) patients presented MM and 90 (27.4%) SMM. Fever was the most frequent clinical manifestation (64.4%), mainly in the MM group (MM: 81.1% vs SMM: 20.0%; p < 0.01). The most frequent species was P. falciparum. Patients with SMM presented fewer cytopenias and a greater number of coinfections due to soil-transmitted helminths, filarial and intestinal protozoa compared to patients with MM. CONCLUSIONS: Imported malaria in our area is closely related to sub-Saharan migration. VFR migrants are the main risk group, highlighting the need for actions aimed at improving disease prevention measures. On the other hand, almost a third of the cases are due to SMM. This fact could justify its systematic screening, at least for those travelers at greater risk. GRAPHIC ABSTRACT: [Image: see text]